Work Overload and Its Impact on Staff Retention Among Non-Teaching Personnel of Public Elementary Schools in the Philippines - Maricar Q Baes; Rose Lyn C Dinglasan; Niña Faye A Patal; Christine Rellama; Jesus Briones; Joanna Paula E Verano (Research Synergy Foundation, 2025)
Effective staff retention strategies are essential in the workplace to address employee turnover, improve work-life balance, and promote employee commitment to the organization. This study examined the impact of work overload on staff retention in public elementary schools in the Philippines, focusing on 148 non-teaching personnel. Employing a descriptive-quantitative research design, data were gathered through a researcher-structured questionnaire formatted in Google Forms and distribution was made online via the personal email addresses of non-teaching personnel. The data were analyzed using frequency, percentage, weighted mean, standard deviation, and Pearson correlation coefficient as statistical tools. The findings revealed that work overload is prevalent, with task demands, time pressure, and role ambiguity identified as critical stressors. However, despite the workload experienced by the non-teaching personnel they are still committed to stay with the organization. Time pressure, work hours, and role ambiguity showed significant correlations with job satisfaction and organizational commitment, while resource availability and task demand exhibited no direct influence on staff retention. These findings suggest that external factors and personal resilience may mitigate the impact of work overload. Based on the findings of the study, a strategy roadmap for improving staff retention is proposed. This study is essential for an organization seeking to improve staff retention and the long-term success created through workload distribution and clarifying roles in the workplace.